2022-RA-945-ESGO Antitumour activity of dostarlimab by PD-L1 and tumour mutation burden in patients with mismatch repair deficient and proficient tumours in the GARNET trial. (20th October 2022) - Banerjee, Susana; André, Thierry; Berton, Dominique; Ellard, Susan L; Jimenez, Begoña; Samouëlian, Vanessa; Gilbert, Lucy; Boni, Valentina; Han, Xinwei; Antony, Grace; Veneris, Jennifer; Oaknin, Ana
Abstract : Introduction/Background: Dostarlimab is a programmed death 1 (PD-1) inhibitor approved as monotherapy in patients with mismatch repair deficient (dMMR) recurrent/advanced endometrial cancer (EC) that has progressed on or after platinum-based chemotherapy or solid tumours that have progressed on or after prior treatment, with no satisfactory alternative treatment options. We report a post hoc analysis of antitumour activity by PDL1 expression and tumour mutational burden (TMB) in patients with dMMR and MMR proficient (MMRp) solid tumours in the GARNET trial. Methodology: GARNET (NCT02715284 ) is a phase 1, multicentre, open-label, single-arm study of dostarlimab in patients with advanced/recurrent solid tumours. Three expansion cohorts enrolled patients based on MMR status: dMMR (A1) and MMRp (A2) advanced/recurrent EC, and dMMR non-EC solid tumours (F). Patients received dostarlimab 500 mg IV Q3W for 4 cycles, then 1000 mg IV Q6W until progression or discontinuation. TMB and PDL1 were exploratory biomarkers. TMB status was determined by FoundationOne test; TMB-high (TMB-H) was defined as ≥10 mutations/Mb. PDL1 expression was determined by combined positive score (CPS) by Ventana assay; PDL1-high (PDL1-H) was defined as CPS ≥1. The study was not powered to assess antitumour activity within subgroups. Results: TMB-H and PDL1-H were common in dMMR solid tumours; PDL1-H was observed in 39.4% of MMRp EC tumours ( table 1 ). Objective response rate (ORR) was higher in patients with TMB-H/PDL1-H tumours (55.6% for all cohorts, combined; Table). Safety for each cohort was previously reported. 1 Conclusion: PDL1-H and TMB-H were frequently observed in the dMMR EC and non-EC cohorts, regardless of tumour type; PDL1-H was also prevalent in MMRp EC tumours. Although not a powered analysis, ORR by BICR per RECIST v1.1 was higher in patients with TMB-H and PDL1-H solid tumours. Across cohorts, dMMR status was predictive of response. Reference: Andre T, et al. Ann Oncol 2021;32 (suppl 5):S829-S866. 991P.